Analytical Report on Urban Crediting Methodology - World Bank (World Bank, Washington, DC, 2020)
With an increasing share of populations dwelling in cities, urban emission reduction is gaining priority at the national level. A high share of greenhouse gas (GHG) emissions in the global footprint is ultimately attributable to urban areas; as such, the effect of carbon lockin further increases the need for immediate action at the urban level. City and regional policy makers are well placed to affect urban emission pathways through city-wide actions. The credits generated from an urban carbon crediting approach may be used for a range of purposes. The two key options are: (1) for use toward the unconditional or conditional targets established through nationally determined contributions (NDC); or (2) use as seed financing to drive engagement with the international investment community or private sector investors.